Conservative treatment of Herlyn-Werner-Wunderlich syndrome: Analysis and long-term follow-up of 51 cases. (August 2022) - Candiani, M.; Vercellini, P.; Ferrero-Caroggio, C.; Fedele, F.; Salvatore, S.; Fedele, L.
Abstract: Objective: The purpose of this study is to analyze the precise anatomical characteristics of a large group of patients with Herlyn-Werner-Wunderlich syndrome together with the long-term follow-up and the reproductive performance. Study design: Retrospective analysis of prospectively collected data. In two tertiary medical centers, from 2008 to 2021, 51 patients with HWWS underwent surgery via the same technique. Presenting symptoms, preoperative investigations, operative management, and long-term follow-up with obstetric outcome were assessed. Results: The surgical procedure was successful in all cases with no major complications recorded. Postoperative course was uneventful. The median follow-up was 6, 5 years, with a range from 6 months to 13 years. After surgery, among 14 patients who sought pregnancies, 12 (85, 71%) were successful. Of these 11 patients had a total of 22 pregnancies, resulting in spontaneous miscarriage in 27% (6/22), premature birth (<37 weeks) in 36% (8/22) and full-term birth in 36% (8/22). Overall the pregnancies demonstrated had a good course. Conclusions: Early diagnosis is essential in establishing prompt and correct surgical treatment.